Hubungan Pengetahuan, Perasaan, dan Tindakan Moral terhadap Perkembangan Akhlak Siswa di MI Karakter Mutiara Bunda Bali saat Pandemi Covid-19 - Hikmah, Rifqikah Durrotul; Zuryani, Nazrina; Mahadewi, Ni Made Anggita Sastri (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2021)
ABSTRACT MI Karakter Mutiara Bunda Bali’s students require character education or moral values. During the Covid-19 pandemic, this study attempted to explore and analyze the link of knowing, feeling, and moral action to students moral development utilizing Lickona’s (1991) character education theory in line with Ratna Megawangi’s (2000) notion, namely the nine pillars of character. The sample size is the same as the entire population of 120 respondents. The data analysis used is correlation test, classical assumption test, and multiple linear regression analysis. The results showed that knowing, feeling, and moral actions have a strong relationship with 70.4% of students' moral development. Of the three concepts, moral action has a major influence on the moral development of students. Keywords: Moral Knowing, Moral Feeling, Moral Action, and Morals